Combining newborn metabolic and genetic screening for neonatal intrahepatic cholestasis caused by citrin deficiency. Issue 3 (29th December 2019) - Lin, Yiming; Liu, Yaru; Zhu, Lin; Le, Kaixing; Shen, Yuyan; Yang, Chiju; Chen, Xigui; Hu, Haili; Ma, Qingqing; Shi, Xueqin; Hu, Zhenzhen; Yang, Jianbin; et al.
Abstract: To evaluate the feasibility of incorporating genetic screening for neonatal intrahepatic cholestasis, caused by citrin deficiency (NICCD), into the current newborn screening (NBS) program. We designed a high‐throughput iPLEX genotyping assay to detect 28 SLC25A13 mutations in the Chinese population. From March 2018 to June 2018, 237 630 newborns were screened by tandem mass spectrometry at six hospitals. Newborns with citrulline levels between 1/2 cutoff and cutoff values of the upper limit were recruited for genetic screening using the newly developed assay. The sensitivity and specificity of the iPLEX genotyping assay both reached 100% in clinical practice. Overall, 29 364 (12.4%) newborns received further genetic screening. Five patients with conclusive genotypes were successfully identified. The most common SLC25A13 mutation was c.851_854del, with an allele frequency of 60%. In total, 658 individuals with one mutant allele were identified as carriers. Eighteen different mutations were observed, yielding a carrier rate of 1/45. Notably, Quanzhou in southern China had a carrier rate of up to 1/28, whereas Jining in northern China had a carrier rate higher than that of other southern and border cities. The high throughput iPLEX genotyping assay is an effective and reliable approach for NICCD genotyping. The combined genetic screening could identify an additional subgroup of patients with NICCD, undetectable by conventional NBS. Therefore, this study demonstrates the viability of incorporating genetic screening for NICCD into the current NBS program.